Deep Surveying of the Transcriptional and Alternative Splicing Signatures for Decidual CD8+ T Cells at the First Trimester of Human Healthy Pregnancy - Zeng, Weihong; Liu, Xinmei; Liu, Zhicui; Zheng, Ying; Yu, Tiantian; Fu, Shaliu; Li, Xiao; Zhang, Jing; Zhang, Siming; Ma, Xiaoling; Liu, Xiao-Rui; Qin, Xiaoli; et al. (Frontiers in Immunology, 2018)
Decidual CD8+ (dCD8) T cells have been proposed to play important roles in immune protection against the invading pathogens and in tolerance toward the growing semi-allogeneic fetus during early pregnancy. However, their phenotypic and functional characteristics remain poorly defined. Here, we performed the first analysis of the transcriptional and alternative splicing (AS) signatures for human first-trimester dCD8 T cells using high-throughput mRNA sequencing. Our data revealed that dCD8 T cells have distinct transcriptional and AS landscapes as compared with their autologous peripheral blood CD8+ (pCD8) T counterparts. Furthermore, human dCD8 T cells were observed to contain CD8-Treg and effector-memory T-cell subsets, and display enhanced functionality in terms of degranulation and cytokine production on a per-cell basis. Additionally, we have identified the novel splice junctions that use a high ratio of the noncanonical splicing motif GC-AG and found that AS is not a major contributor to the gene expression-level changes between paired pCD8 and dCD8 T cells. Together, our findings not only provide a comprehensive framework of the transcriptional and AS landscapes but also reveal the functional feature of human dCD8 T cells, which are of great importance in understanding the biology of these cells and the physiology of human healthy pregnancy.